Entangled Media Histories: A Response. Issue 1 (2nd January 2017) - Griffen-Foley, Bridget
Abstract : This commentary responds to the research report by Marie Cronqvist and Christoph Hilgert on the value of transnational and transmedial approaches in media historiography. It reflects on my introduction to the concept of 'entangled media histories', and its potential application to the study of the history of media in Australia and the Asia-Pacific as the field continues to grow in the region, as sketched out in the piece. It considers the value of the historiographical approach to the Asia-Pacific, and also some of the challenges, principally language barriers, and including the national construction of many digital and other media history resources.